Discrete Morse Theoretic Algorithms for Computing Homology of Complexes and Maps - Harker, Shaun; Mischaikow, Konstantin; Mrozek, Marian; Nanda, Vidit (Foundations of computational mathematics, 2014)
We provide explicit and efficient reduction algorithms based on discrete Morse theory to simplify homology computation for a very general class of complexes. A set-valued map of top-dimensional cells between such complexes is a natural discrete approximation of an underlying (and possibly unknown) continuous function, especially when the evaluation of that function is subject to measurement errors. We introduce a new Morse theoretic preprocessing framework for deriving chain maps from such set-valued maps, and hence provide an effective scheme for computing the morphism induced on homology by the approximated continuous function.